2019
DOI: 10.1149/2.0981915jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Pyrolysis of Si/Polyacrylonitrile Composites as an Unconventional Approach to Fabricate High Performance Lithium Ion Battery Negative Electrodes

Abstract: High performance Si/polyacrylonitrile (PAN) composite negative electrodes are fabricated by a robust process of oxidative pyrolysis at a temperature between 250 and 400°C. Multiple techniques are employed to investigate the structural, chemical, and mechanical properties of the Si/PAN composite electrodes before and after oxidative pyrolysis. With increasing temperature, oxidation, dehydration, aromatization, and intermolecular crosslinking take place in PAN, resulting in a stable cyclized structure which func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Silicon (Si) or silicon (SiO 2 ) is a popular electrode material for LIBs due to its high theoretical capacity of 3579 mAh g −1[ 137 , 138 , 139 , 140 ] or 4200 mAh g −1 . [ 141 ] Further, safety performance and suitable operating potential make it promising candidate for practical batter application.…”
Section: Sulfurized Polyacrylonitrile Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon (Si) or silicon (SiO 2 ) is a popular electrode material for LIBs due to its high theoretical capacity of 3579 mAh g −1[ 137 , 138 , 139 , 140 ] or 4200 mAh g −1 . [ 141 ] Further, safety performance and suitable operating potential make it promising candidate for practical batter application.…”
Section: Sulfurized Polyacrylonitrile Compositesmentioning
confidence: 99%
“…Furthermore, the pPAN/SeS 2 prepared by applying a high voltage (17 kV) exhibited a discharge capacity of 871 mAh g −1 at 4 A g −1 , which remained at 633 mAh g −1 after 2000 cycles maintaining a very low capacity decay rate (0.014% per cycle) (Figure 13g). [136] Silicon (Si) or silicon (SiO 2 ) is a popular electrode material for LIBs due to its high theoretical capacity of 3579 mAh g −1 [137][138][139][140] or 4200 mAh g −1 . [141] Further, safety performance and suitable operating potential make it promising candidate for practical batter application.…”
Section: Metal Oxides or Sulfide/sulfurized Polyacrylonitrile Compositesmentioning
confidence: 99%
“…41 Another direction that has been explored is the use of carbonized binders, which have improved electrical conductivity and helped prolong cycle life in silicon electrodes. [42][43][44] There are few reports on the expansion of these electrodes, but Mukhan et al have reported that silicon electrodes containing pyrolyzed poly ether imide (PEI) binder showed significantly less expansion in the first two cycles than electrodes with a conventional polyvinylidene difluoride (PVDF) binder, which was attributed to the superior binder-silicon bonding between silicon and PEI than with PVDF. 45 In addition, electrode reversibility was improved with the pyrolyzed PEI binder, compared to electrodes made with PVDF or sodium-carboxymethyl cellulose binders.…”
mentioning
confidence: 99%